A learning journey. A narrative-autoethnographical reflection - Jõgi, Larissa (Adult Education Discourses, 2023)
This essay is based on autoethnography and reflects on experience, meaningful moments, positive turning points in the author’s learning journey as a scholar, university teacher and adult educator. Becoming and being somebody has been a long, lifelong, and emotional process. The author asked this question: what does the learning journey mean and why is it meaningful for her? The essay shows how the author reflected on the experience, and used a personal diary, memos, and notes. For the reflective writing, the author based themself here on a narrative and autoethnographic approach, having in mind concentrating more on peak, positive and meaningful rather than negative experience. The final writing process was a kind of retelling that involves re-reading the diary and rewriting this essay in the form of a personal narrative. To make the essay coherent the author relied upon the structure of the narrative.